Assessing chikungunya's economic burden and impact on health-related quality of life: Two systematic literature reviews. - Giorgia Tiozzo; Adrianne M de Roo; Gabriel S Gurgel do Amaral; Hinko Hofstra; Gerard T Vondeling; Maarten J Postma (PLoS Neglected Tropical Diseases)
Background Chikungunya virus (CHIKV), transmitted through Aedes mosquitoes, has witnessed a global surge in distribution and outbreaks, posing a significant public health threat. This study conducted two systematic literature reviews (SLRs) to examine the socio-economic burden associated with chikungunya. Methods Two SLRs were conducted employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 (PRISMA 2020) standards. The SLRs covered electronic databases, grey literature, and bibliographic searches. Inclusion criteria were guided by the PICOS (Population, Intervention, Comparator, Outcomes, Study type) framework. Findings A total of 34 studies on cost and resource use and 37 studies on health-related quality of life (HRQoL) were included. Direct costs, driven by hospitalization, consultations, diagnostics, and drugs, were frequently reported, with significant variability across studies. Indirect costs, mainly attributed to absenteeism, constituted a substantial portion of the total economic burden. HRQoL studies consistently revealed high pain levels and diminished physical functioning among chikungunya patients, particularly in chronic cases, where these impacts persisted for months to years. Conclusions This study highlights the significant economic and public health impact of chikungunya, driven by high treatment costs, productivity losses, and chronic disability. Despite the severity of the disease, limited awareness regarding the severity and economic burden, particularly in resource-limited regions, persists. Our findings underscore the need for targeted public health strategies, standardized management approaches, and increased research to better understand the socio-economic burden of the disease and inform effective interventions.